2002
DOI: 10.1016/s0735-1097(02)02122-8
|View full text |Cite
|
Sign up to set email alerts
|

Deoxyribonucleic acid damage/repairproteins are elevated in the failing human myocardium due to idiopathic dilated cardiomyopathy

Abstract: In this study, apoptosis could not be detected in the failing myocardium owing to idiopathic dilated cardiomyopathy. In contrast, failing myocardium was characterized by active DNA repair that was associated with elevated LV wall stress and activation of the inducible NO synthase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
28
2
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 31 publications
5
28
2
3
Order By: Relevance
“…Our data support many previous studies where cell oxidative/nitrosative stress was shown to be involved in the development of cardiac hypertrophy (reviewed in Ref. 21) and in many other reports where failing hearts were found to be associated with increased activity of the PARP enzyme (1,24,32). These results strengthen the notion that PARP inhibition as monotherapy, or as a combination therapy that includes activation of the Sir2␣, may represent a novel approach for the management of heart failure.…”
Section: Discussionsupporting
confidence: 91%
“…Our data support many previous studies where cell oxidative/nitrosative stress was shown to be involved in the development of cardiac hypertrophy (reviewed in Ref. 21) and in many other reports where failing hearts were found to be associated with increased activity of the PARP enzyme (1,24,32). These results strengthen the notion that PARP inhibition as monotherapy, or as a combination therapy that includes activation of the Sir2␣, may represent a novel approach for the management of heart failure.…”
Section: Discussionsupporting
confidence: 91%
“…15,16 These DNA repair enzymes, PCNA and Ref-1, were recently reported to be increased in the nucleus of myocytes of hearts with DCM. 17 In the present study, strong correlations were noted between expressions of PCNA, Ref-1, and 8-OHdG, suggesting that oxidative DNA damage might contribute to increased DNA repair.…”
Section: Discussionsupporting
confidence: 58%
“…The NO-mediated increase in DNA-PKcs pathway not only plays an important role in tumour DNA repair [51], but may also play an important role in other tissue damage processes which involve NOmediated stress [52], [53]. For example, failing myocardium, (advanced heart failure due to idiopathic dilated cardiomyopathy) undergoes active DNA repair, where DNA-PKcs expression is strongly correlated with iNOS expression (r=0.53, p < 0.01) [53].…”
Section: No and Tumour Cell Angiogenesismentioning
confidence: 99%
“…For example, failing myocardium, (advanced heart failure due to idiopathic dilated cardiomyopathy) undergoes active DNA repair, where DNA-PKcs expression is strongly correlated with iNOS expression (r=0.53, p < 0.01) [53]. Given the fact that one of the major substrates of DNA-PKcs is p53 [54] and DNA-PKcs itself is subjected to ADP-ribosylation by PARP, it is possible that NO-mediated DNA damage and repair could play a significant role in tumour development (Fig 3).…”
Section: No and Tumour Cell Angiogenesismentioning
confidence: 99%